VALIDITY AND RELIABILITY OF ADOLESCENT LEARNING STYLE INSTRUMENT (IGBR) DEVELOPMENT: RASCH MODEL ANALYSIS - Anbiya, Delvira Nur; Imaddudin, Aam; Sulistiana, Dewang (Jurnal Kajian Pendidikan dan Psikologi, 2025)
Learning style is the way each learner begins to contribute to processing, processing and retain new and difficult information. The development of an adolescent learning style instrument helps students to identify learning style patterns based on the theory used. However, the limitations of the adolescent learning style instrument have only been tested on junior high school students. This research aims to develop, test the validity and reliability of an adolescent learning style instrument using the Winstep software RASCH model. Participants in this research were 840 students at the junior high school level in Tasikmalaya City and Regency. The results of the item validity test using the RASCH Model program Winstep software show that all items are valid (126 items) with the Outfit Mean Square (MNSQ) value. The results of the reliability test of the adolescent learning style instrument, consisting of 126 items, were declared valid; the Cronbach's Alpha value was 0.85, which is in the very good category. The Person Reliability value of 0.87 is at a good level. And the Item Reliability value of 0.99 shows that the level of item consistency is in the special category.